Chymase uptake by cardiomyocytes results in myosin degradation in cardiac volume overload. Issue 4 (April 2019) - Powell, Pamela C.; Wei, Chih-Chang; Fu, Lianwu; Pat, Betty; Bradley, Wayne E.; Collawn, James F.; Dell'Italia, Louis J.
Abstract: Background: Volume overload (VO) of isolated mitral regurgitation (MR) or aortocaval fistula (ACF) is associated with extracellular matrix degradation and cardiomyocyte myofibrillar and desmin breakdown. Left ventricular (LV) chymase activity is increased in VO and recent studies demonstrate chymase presence within cardiomyocytes. Here we test the hypothesis that chymase within the cardiomyocyte coincides with myosin and desmin breakdown in VO. Methods and results: Aortocaval fistula (ACF) was induced in Sprague Dawley (SD) rats and was compared to age-matched sham-operated rats at 24 hours, 4 and 12 weeks. Immunohistochemistry (IHC) and transmission electron microscopy (TEM) immunogold of LV tissue demonstrate chymase within cardiomyocytes at all ACF time points. IHC for myosin demonstrates myofibrillar disorganization starting at 24 hours. Proteolytic presence of chymase in cardiomyocytes is verified by in situ chymotryptic tissue activity that is inhibited by pretreatment with a chymase inhibitor. Real-time PCR of isolated cardiomyocytes at all ACF time points and in situ hybridization demonstrate endothelial cells and fibroblasts as a major source of chymase mRNA in addition to mast cells. Chymase added to adult rat cardiomyocytes in vitro is taken up by a dynamin-mediated process and myosin breakdown is attenuated by dynamin inhibitor, suggesting that chymase uptake is essential for myosin breakdown. In a previous study in the dog model of chronic MR, the intracellular changes were attributed to extracellular effects. However, we now demonstrate intracellular effects of chymase in both species. Conclusion: In response to VO, fibroblast and endothelial cells produce chymase and subsequent cardiomyocyte chymase uptake is followed by myosin degradation. The results demonstrate a novel intracellular chymase-mediated mechanism of cardiomyocyte dysfunction and adverse remodeling in a pure VO.